PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN LANGGENG LAUNDRY DI KUTA, BADUNG - Putra, IGN Marta Eka; Sariyathi, Ni Ketut (E-Jurnal Manajemen; Vol 4 No 5 (2015), 2015)
Job satisfaction an important element in improving employee performance for achieving high level of employees job satisfaction, a companies need to consider factors that affect job satisfaction of the employees. In this study predictor which are considered to affect job satisfaction are transformational leadership, work environment and compensation. The number of samples is 98 employees. Techique of analysis used in this study is multiple linear regression analysis. The result show that transformational leadership style, work environment and compensation for partially and simultaneous affect employee job satisfaction. Out of the three predictors, compensation emerges as dominant predictor of employees job satisfaction. To improve job satisfaction Laundry Langeng corporate leaders should improve relations with employees in order to increase job satisfaction, attention to the work environment and a better compensation.
Keywords: Transformasional, Lingkungan Kerja, Kompensasi, Kepuasan Kerja